Effect of Basic Fibroblast Growth Factor in Perifascial Areolar Tissue Transplant - Oshima, Junya; Shibuya, Yoichiro; Sasaki, Kaoru; Sekido, Mitsuru (Indian Journal of Plastic Surgery, 2024)
Background Perifascial areolar tissue (PAT) transplant is a technique in which a sheet of connective tissue on the fascia is harvested and transplanted to the wound bed. PAT engraftment fails when the exposed area of tendons, bones, or artificial materials is large. On the other hand, combination of tissue transplant and basic fibroblast growth factor (bFGF) improves the survival rate of the transplanted tissue.Materials and Methods A wound model was created in which the artificial material was exposed on rats' backs. All the rats underwent PAT transplant, but the rats were divided into two groups according to the PAT processing method beforehand. In one group, the PAT was immersed in water for injection before transplant (bFGF[–] group), and in the other group, the PAT was immersed in bFGF product (bFGF[+] group). Specimens were collected 7 days after surgery to assess the histologic thickness of the PAT and the gene expression in the PAT.Results The thickness of the PAT in the tissue slices was significantly higher in the bFGF(+) group than in the bFGF(–) group. Expressions of CD34 and COL3A1 were significantly higher in the bFGF(+) group than in the bFGF(–) group.Conclusion The results of this study indicate that adding bFGF to the PAT transplant may promote PAT engraftment and wound healing by increasing angiogenesis and may increase granulation formation, which may result in a stronger covering that prevents the prosthesis from being exposed.
Keywords: perifascial areolar tissue; loose connective tissue; basic fibroblast growth factor; ulcer